131 A REVIEW OF FRAILTY AND PATIENT DISCHARGE OUTCOMES IN A NEWLY FORMED PHYSIOTHERAPY TEAM IN A LEVEL 4 TEACHING HOSPITAL. (18th November 2021) - Magner, S; Collins, L; Quaid, S; Burke, P; Lynch, A; Horan, E
Abstract: Background: The clinical frailty score (CFS) is a 9 point validated outcome measure used to measure function, mobility, cognition and co-morbidities in patients aged 65 or older. The physiotherapy department was restructured due to COVID-19 pandemic. This resulted in the formation of a mixed specialty team which consisted of Frailty Intervention Team (FIT), Medical Respiratory, Acute Medicine Service, Orthopaedics, General Rehabilitation and Care of the Older Person (COTOP). This service review aimed to identify frailty using the CFS across services and to compare CFS versus age, length of stay, falls history and discharge outcomes. Methods: The CFS data was collected over two weeks. Inclusion criteria included patients who scored ≥4 on the CFS. Exclusion criteria included patients aged under 65. Variables such as age, history of falls, LOS and discharge destinations were compared across all services using Microsoft Excel. Results: 166 patients were included, the average CFS was 5.24 and the average age was 77.2 years. COTOP had the oldest (Av. age 85.4), frailest (Av. CFS 6.1) and longest avLOS (25.3 days) across all services. Frailty was prevalent across all services, with 81% of patients on the medical respiratory service classed as frail. Patients who scored a CFS of ≥4 had higher falls risk and greater LOS. Of the medical respiratory cohort only 12% were discharged to rehabilitation with 77% discharged home. Orthopaedics had the highest percentage of patients discharged to rehabilitation (44%), followed by the general rehabilitation (34%). Only 14% of the COTOP patients were transferred to rehabilitation. Conclusion: A high incidence of frailty and falls history was identified across all services. Patients who scored lower on the CFS resulted in reduced LOS and were more likely to be discharged directly home. Proactive screening and detection of frailty allows for targeted interventions that may improve outcomes and inform early discharge planning.